2008
DOI: 10.1038/sj.ijo.0803795
|View full text |Cite
|
Sign up to set email alerts
|

Obesity reduces the bioavailability of nitric oxide in juveniles

Abstract: Objective: There is growing evidence that nitric oxide (NO) is critically involved in obesity and its clinical consequences like cardiovascular disease, hypertension and diabetes. We hypothesize that NO is already involved in the pathophysiology of juvenile obesity. We here determined the role of NO, its metabolites arginine and citrulline in obese and normal weight children. Design: We investigated 57 obese and 57 normal weight age-and gender-matched juveniles. Various clinical parameters as well as body meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 29 publications
5
83
3
5
Order By: Relevance
“…Plasma NO x levels are increased in obese children with metabolic syndrome and in New Zealand Obese mice, 29,30 whereas they are decreased in obese teenagers with metabolic syndrome. 31 Other laboratories have observed that plasma NO x was increased in rats that were fed a highfructose diet for 8 and 13 weeks. 32,33 However, plasma NO x was decreased in another rat model treated with 10% fructose in drinking water for 6 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…Plasma NO x levels are increased in obese children with metabolic syndrome and in New Zealand Obese mice, 29,30 whereas they are decreased in obese teenagers with metabolic syndrome. 31 Other laboratories have observed that plasma NO x was increased in rats that were fed a highfructose diet for 8 and 13 weeks. 32,33 However, plasma NO x was decreased in another rat model treated with 10% fructose in drinking water for 6 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, it has been postulated that a resistant state may lead to hypertension due to the failure of the nitric oxide-mediated vasodilator activity of the insulin hormone on endothelial cells 35 . It has been reported that this effect is diminished in obese individuals 36 . It is reasonable to assume that such failure in the insulin action, coupled to independent events of excessive renal reabsorption and/or consumption of sodium as well as persistence of sympathetic activity can contribute to the rise of the blood pressure.…”
Section: Ferreira Et Al Cardiovascular Risk Factors In Brazilian Chilmentioning
confidence: 92%
“…Paradoxically, cross-sectional studies indicate that exerciseinduced reductions in FMD are not apparent in trained populations who regularly engage in exercise. 12,16 Given that obesity and sedentary lifestyle independently contribute to low-grade inflammation 17,18 and reduced NO bioavailability, 13,19 it is plausible to hypothesize that inflammation may be a critical factor mediating postexercise reductions in FMD among obese and sedentary populations.…”
Section: Introductionmentioning
confidence: 99%